286 Gestation length as a weak predictor of yearling pulmonary arterial pressure and risk of developing high altitude disease in Angus cattle at high elevation. (7th December 2018) - Foxworthy, H; Enns, R; Speidel, S; Thomas, M; Holt, T
Abstract: Pulmonary arterial pressure (PAP) score is used to determine the risk for high altitude disease (HAD), a disorder of hypoxia-induced pulmonary hypertension, in beef cattle at high elevation. Given lung development occurs in utero, gestation length (GL) may be a source of variation in PAP score and a predictor of an animal's susceptibility to HAD later in life. Therefore, the objective was to determine the relationship between GL and PAP in Angus cattle at high elevation. The PAP and GL observations were obtained from the Colorado State University's Beef Improvement Center near Saratoga, Wyoming (elevation of 2, 150 m) using breeding and calving records from the years 2007 to 2016 (n = 1, 991 calves). Gestation length was calculated for individuals and verified, with ultrasound up to 50 days after artificial insemination, and subsequent calving records. The data included PAP measurement (43.13 ± 11.23 mmHg), GL (276.8 ± 5.77 days), age of dam (AOD, 5.892 ± 3.30 years), birth year, and calf sex at birth. The relationship between calf GL and PAP was evaluated using both a Pearson correlation coefficient and a simple linear regression model. The linear model for PAP as the dependent variable included GL as a covariate, and sex, birth year, and AOD as categorical fixed effects. The phenotypic correlation was estimated as -0.005 (P > 0.83) between PAP and GL. Regression results suggest no effect of GL ( P > 0.50) or AOD ( P > 0.85) on yearling PAP score. However, birth year and sex were significant factors ( P < 0.001) on yearling PAP score. Results indicate that GL likely has no effect on yearling PAP and gestational age at birth should not increase an animal's susceptibility to developing HAD into adulthood.